Proceso de atención de enfermería en paciente de 7 años con criptorquidia. - Pico Zabala, Kerly Lissette (2020)
The current clinical case was carried out on a seven-year-old male patient, who attended this health home in the company of his mother, with a first-level medical reference, with a diagnosis from birth of bilateral cryptorchidism classifying non-testicles. palpable congenital descendants, at the time of medical evaluation, hospital admission is decided, patient refers unilateral left testicular pull, with pain of two months evolution that intensifies when walking and standing, with visual analog scale with intensity of severe pain 10 / 10, with expressive crying behavior, facial expression of pain and posture to avoid pain, we proceed to reprogrammed surgery (orchidopexy). In cryptorchidism, genetic, neurological, anatomical and hormonal factors influence the embryonic process of testicular descent and when there is a failure in one of these factors, the result may be the lack of testicular descent of one or both testicles towards the scrotum. After the surgical treatment called orchidopexy, the surgical wound has a good appearance, with no signs of apparent infection, which was achieved thanks to the nursing care, feeding, mobilization, healing and optimal antibiotic treatment, when inspecting the scrotal bag, a scrotal bag was observed symmetrical, and the two testicles can be palpated in their normal position, their clinical status after treatment is timely and expected, there is improvement and disappearance of signs and symptoms that they presented before surgery. Patient must continue with their annual controls to verify the results of the treatment.